2018
DOI: 10.3847/1538-4357/aad3c9
|View full text |Cite
|
Sign up to set email alerts
|

CO (7−6), [C i] 370 μm, and [N ii] 205 μm Line Emission of the QSO BRI 1335-0417 at Redshift 4.407

Abstract: We present the results from our Atacama Large Millimeter/submillimeter Array (ALMA) imaging observations of the CO (7−6), [C i] 370 µm (hereafter [C i]) and [N ii] 205 µm (hereafter [N ii]) lines and their underlying continuum emission of BRI 1335-0417, an infrared bright quasar at z = 4.407. At the achieved resolutions of ∼1.1 ′′ to 1.2 ′′ (or 7.5 to 8.2 kpc), the continuum at 205 and 372 µm (restframe), the CO (7−6), and the [C i] emissions are at best barely resolved whereas the [N ii] emission is well reso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 90 publications
(130 reference statements)
3
25
1
Order By: Relevance
“…To make the estimates for the QSO and SMG, we used the infrared luminosities from Salomé et al (2012). Other estimates from the literature are a few times higher (Wagg et al 2014;Lu et al 2018) and would yield values that have greater consistency with the best fit shown in the figure.…”
Section: H 2 O: Ir-pumping and Energy Dissipationmentioning
confidence: 99%
See 1 more Smart Citation
“…To make the estimates for the QSO and SMG, we used the infrared luminosities from Salomé et al (2012). Other estimates from the literature are a few times higher (Wagg et al 2014;Lu et al 2018) and would yield values that have greater consistency with the best fit shown in the figure.…”
Section: H 2 O: Ir-pumping and Energy Dissipationmentioning
confidence: 99%
“…BR 1202-0725 is a well-studied, unlensed group composed of a quasi-stellar object (QSO), a sub-millimeter galaxy (SMG;McMahon et al 1994;Smail et al 1997), and two Lyα emitters (LAEs; e.g., Hu et al 1996). Both the QSO and SMG are very luminous IR emitters, ∼10 13 L , and the system has been observed in a wide range of molecular and atomic lines (Omont et al 1996;Benford et al 1999;Salomé et al 2012;Carilli et al 2013;Lu et al 2017aLu et al , 2018, and references therein). Based on an excess in the wing of the line profile of [CII], Carilli et al (2013) estimated an outflow rate in the atomic gas from the QSO ofṀ out ∼80 M yr −1 and concluded that the gas depletion time due to this outflow is ∼600 Myrs, a factor of 10 longer than the gas consumption time due to star formation.…”
Section: Introductionmentioning
confidence: 99%
“…At high-z, observations of the [Nii] 205 µm line is largely limited to z > 3.9, where the line is red-shifted to wavelengths longer than 1mm, making ground based observations possible due to the more transmissive and stable atmosphere, with lower receiver noise temperatures. The current sample where this emission line is detected consists of twelve highly star-forming galaxies (Decarli et al 2012(Decarli et al , 2014Combes et al 2012;Rawle et al 2014;Nagao et al 2012;Béthermin et al 2016;Pavesi et al 2016Pavesi et al , 2018bLu et al 2018), and there are at least five additional non-detections (see Walter et al 2009;Riechers et al 2013a).…”
Section: Introductionmentioning
confidence: 97%
“…[Cii]/[Nii] line luminosity ratios observed in high redshift galaxies to-date as a function of their FIR luminosityDe Breuck et al 2014;Béthermin et al 2016;Rawle et al 2014;Combes et al 2012;Riechers et al 2013Riechers et al , 2014Capak et al 2015;Wagg et al 2010;Umehata et al 2017;Lu et al 2018;Pavesi et al 2018b).For comparison we also show a sample of local ULIRGs from Farrah et al (2013) (using the [Nii] 122 µm line) and LIRGs with [Nii] (using the [Nii] 205 µm line) from Zhao et al (2016) and [Cii] from Díaz-Santos et al (2013). The range of ratios in dwarfs (Cormier et al 2015) (using the [Nii] 122 µm line) is shown as a cyan band.…”
mentioning
confidence: 99%